DESIGNING OF BREAST CANCER AWARENESS CAMPAIGNS IN YOUNG WOMEN IN MOTION GRAPHIC MEDIA - ZULFA JUM’AINI, Dr. Syafwandi, M.Sn., Dini Faisal, S.Ds., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Breast cancer is one of the causes of death in women, mostly because the patient comes at an advanced stage, and the symptoms are not perceived as a grave. The design of breast cancer risk awareness campaigns in adolescent girls in motion graphic media, aims to increase the awareness of young women against breast cancer is equipped with illustrations, text, colors, and audio. The purpose of designing this social campaign is expected to make young women sensitive and attention to the symptoms of breast cancer from an early age.The design method used by the author is started from data collection through interview and literature study. The design methodology in breast cancer awareness campaigns for young women uses SWOT analysis (Strength, Weakness, Opportunity, Treatment). The delivery of information and messages in motion graphics is presented in an interesting form. The use of motion graphics contains moving audio and visuals that eliminate audience saturation when listening to information on the social campaigns that are aired.Keywords: Motion graphic, Danger of breast cancer, Young women.